2002
DOI: 10.1103/physreve.66.021709
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the nonlinear dielectric properties of a nematogenic compound dissolved in a nonpolar medium

Abstract: The nonlinear dielectric spectra of 4-(trans-4'-n-hexylcyclohexyl)isothiocyanatobenzene (C6H13CyHx Ph NCS, 6CHBT) in benzene solutions were recorded in the whole concentration range up to an appearance of the two-phase isotropic and nematic region (0.82 mole fraction of 6CHBT, at 25 degrees C). Two electric fields: (i) the field of high strength (110 kV/m) and low frequency (85 Hz) causing the dielectric nonlinearity, and (ii) the probing field of low strength and high frequency (100 kHz-3 GHz), were used. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…In the work of Kedziora et al [12] the coexistence of nematic and isotropic phases in 6CHBT liquid crystal dissolved in a nonpolar medium (benzene) was observed in the vicinity of the temperature of the isotropic-nematic transition. Due to the existence of a short-range orientational order of the mesogenic molecules (6CHBT), pseudonematic domains (droplets of 500-1000 nm in size depending on the temperature) were formed in the isotropic phase.…”
Section: Introductionmentioning
confidence: 97%
“…In the work of Kedziora et al [12] the coexistence of nematic and isotropic phases in 6CHBT liquid crystal dissolved in a nonpolar medium (benzene) was observed in the vicinity of the temperature of the isotropic-nematic transition. Due to the existence of a short-range orientational order of the mesogenic molecules (6CHBT), pseudonematic domains (droplets of 500-1000 nm in size depending on the temperature) were formed in the isotropic phase.…”
Section: Introductionmentioning
confidence: 97%
“…Another study [20] was inspired by the work of Kedziora et al [21], where a coexistence of nematic and isotropic phases was observed in 6CHBT dissolved in a nonpolar medium (benzene) in the vicinity of the isotropic-to-nematic phase transition temperature.…”
Section: The Structural Transitions In 6chbt-based Ferronematic Dropletsmentioning
confidence: 99%
“…As far as the order parameter or r-EEM is concerned, both can be reduced effectively either by increasing the temperature or by increasing the concentration of some nonmesogenic isotropic liquid solvent. 1012 The latter is the indispensable element of our novel approach. In this paper, our novel approach shows the existence of BPs over a wide range of temperature Δ T = 28 °C (290–318 K) including the room temperature.…”
Section: Introductionmentioning
confidence: 99%